Long-Term Survival in a Patient with Pulmonary Lymphangioleiomyomatosis. Issue 5 (3rd October 2002) - Reid, John K; Rees, Henrike; Cockcroft, Donald
Abstract : A patient with pulmonary lymphangioleiomyomatosis was diagnosed more than 22 years after the onset of symptoms by a thoracoscopic lung biopsy, after a high resolution computerized tomogram of the chest was highly suggestive of the disease. After nearly 30 years since the onset of her symptoms, the patient leads a relatively normal life with only mildly abnormal lung function and has minimal reduction in her exercise tolerance. There have been few reports of patients surviving for such a long time after the onset of this disease; the literature suggests that most patients die within 15 years of symptom onset.